An Ecological Study of Determinants of The Incidence of Tuberculosis in Malang Raya Area - Lucky Radita Alma; Vita Olivionita; Hartati Eko Wardani (Preventia : The Indonesian Journal of Public Health, 2024)
The Malang Raya area (Batu City, Malang City, and Malang Regency) is one of the areas in East Java where the TB rate remains quite high. It is 3,461 cases in 2020. This study aimed to find out the correlation between coverage of healthy houses, coverage of households with healthy lifestyle, population density, air temperature, humidity, and rainfall with the incidence of tuberculosis in Malang Raya in 2021. The study used an ecological study design approach. Secondary data were collected from the Health Office and the Central Bureau of Statistics (Badan Pusat Statistika/BPS) of Malang City, Malang Regency and Batu City. Data were analyzed using Pearson Product Moment and Spearman's rho test. The result of the study indicate the correlation among the coverage of healthy houses and coverage of households with healthy lifestyle correlates with the incidence of tuberculosis in Malang Raya in 2021.